Pengaruh Kreativitas Mengajar Guru Akuntansi terhadap Tingkat Pemahaman Siswa Kelas XI SMA Negeri 1 Waipia - Maslebu, Fiona; Rehalat, Aminah; Ubra, Franklin William (Jurnal Pendidikan Ekonomi, 2023)
Teacher creativity in instruction plays a vital role in enhancing students' understanding in accounting subjects at the senior high school level. This study aims to determine the effect of accounting teachers' teaching creativity on the level of understanding among eleventh-grade students at SMA Negeri 1 Waipia. The research utilized a descriptive quantitative approach, with data collected through questionnaires administered to 30 students selected from the eleventh-grade IPS class. Data were analyzed using simple regression to examine the relationship between teaching creativity and student understanding. The results indicate a positive and significant influence of teachers’ creative teaching methods on students’ comprehension, particularly through varied techniques, effective use of media, and motivational skills. The findings highlight the need for continuous innovation in accounting instruction. It is recommended that teachers consistently enhance their teaching creativity to foster a more engaging and effective learning environment, thereby improving students’ understanding and learning outcomes